S1222a—The Largest Marsquake Detected by InSight - Taichi Kawamura; John F. Clinton; Géraldine Zenhäusern; Savas Ceylan; Anna C. Horleston; Nikolaj L. Dahmen; Cecilia Duran; Doyeon Kim; Matthieu Plasman; Simon C. Stähler; Fabian Euchner; Constantinos Charalambous; et al. (Geophysical Research Letters, 2023)
Abstract NASA's InSight has detected a large magnitude seismic event, labeled S1222a. The event has a moment magnitude of MWMa4.7, with five times more seismic moment compared to the second largest event. The event is so large that features are clearly observed that were not seen in any previously detected events. In addition to body phases and Rayleigh waves, we also see Love waves, minor arc surface wave overtones, and multi‐orbit surface waves. At long periods, the coda event exceeds 10 hr. The event locates close to the North‐South dichotomy and outside the tectonically active Cerberus Fossae region. S1222a does not show any evident geological or tectonic features. The event is extremely rich in frequency content, extending from below 1/30 Hz up to 35 Hz. The event was classified as a broadband type event; we also observe coda decay and polarization similar to that of very high frequency type events.